Outscourcing Menurut Hukum Ketenagakerjaan - Berkat Sama Hulu; Rochim Rochim (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
The employment relationship that occurs between workers and employers which arises due to the existence of a work agreement is actually theoretically the right of the entrepreneur and the right of the worker to start or end it. However, for workers, the legal relationship with employers is always in a subordinate relationship or a relationship where the worker's position is lower than that of the entrepreneur or employer. For outsourcing workers, this becomes even worse because the workers do not have a working relationship with the employing company. The implementation of outsourcing several years after the issuance of Law Number 13 of 2003 concerning Manpower still experienced various weaknesses, mainly due to the lack of regulations issued by the Government as well as injustice in the implementation of work relations between employers and workers. However, basically the practice of outsourcing cannot be avoided by employers, let alone workers. This is because entrepreneurs with the enactment of Articles 64 to Article 66 of Law no. 13 of 2003 concerning Manpower, legalized implementing outsourcing practices without paying attention to things prohibited by law. This research aims to find out how the implementation of Law no. 13 of 2003 concerning Employment in outsourcing practices and the implementation of work protection and work conditions for outsourced workers/laborers after Constitutional Court Decision No. 27/PUU-IX/2011. The method used is a normative juridical approach. The normative juridical research method is legal research that uses secondary data sources. As juridical legal research using labor protection legal principles, especially in Law Number 13 of 2003 concerning Employment. The results of this research state that the outsourcing practice of handing over part of the work implementation to another company through a work contract agreement generally does not implement the terms and conditions of outsourcing as regulated in Law Number 13 of 2003 concerning Manpower and in the considerations and decisions in the case. Application No. 27/PUU-IX/2011, the Constitutional Court did not declare the outsourcing system as a prohibited system in business relations and work relations between workers/laborers and entrepreneurs so that Article 64 of Law no. 13 of 2003.